2021
DOI: 10.3389/fmars.2021.625477
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria From the Southern Gulf of Mexico: Baseline, Diversity, Hydrocarbon-Degrading Potential and Future Applications

Abstract: The Gulf of Mexico Research Consortium (Consorcio de Investigación del Golfo de México (CIGoM), 2020) was founded in 2015 as a consortium of scientific research and consulting services, specializing in multidisciplinary projects related to the potential environmental impacts of natural and human-induced oil spills in marine ecosystems, to understand and act in the case of possible large-scale oil spills in the Gulf of Mexico. CIGoM comprises more than 300 specialized researchers trained at the most recognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 154 publications
(216 reference statements)
0
11
0
Order By: Relevance
“…The benzoate degradation pathway has been commonly found in hydrocarbon-degrading marine bacteria in the Gulf of Mexico ( Muriel-Millán et al, 2019 ; Rodríguez-Salazar et al, 2021 ). Raggi et al (2020) reported the presence of recognized hydrocarbon-degrading bacteria and their metabolic potential through aerobic and anaerobic pathways in sediment samples collected from depths of 1,320, 2,966, and 3,010 m. The high diversity of Rieske oxygenases observed in the northern samples indicates potential for the degradation of diverse aromatic compounds, such as benzoate, benzene, toluene, phthalate, naphthalene, or biphenyl under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The benzoate degradation pathway has been commonly found in hydrocarbon-degrading marine bacteria in the Gulf of Mexico ( Muriel-Millán et al, 2019 ; Rodríguez-Salazar et al, 2021 ). Raggi et al (2020) reported the presence of recognized hydrocarbon-degrading bacteria and their metabolic potential through aerobic and anaerobic pathways in sediment samples collected from depths of 1,320, 2,966, and 3,010 m. The high diversity of Rieske oxygenases observed in the northern samples indicates potential for the degradation of diverse aromatic compounds, such as benzoate, benzene, toluene, phthalate, naphthalene, or biphenyl under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that geographic location, latitude, and pH are determining factors in the diversity of biosynthetic genes and environmental microbiomes [ 64 , 65 , 66 ]. The GoM is one of the marine ecosystems most affected by the uncontrolled extraction of hydrocarbons and countless oil spills [ 67 ], which is why its bacterial biodiversity is distinctive and largely influenced by environmental factors specific to the region, especially to the presence of hydrocarbons [ 68 ]. The natural conditions of the ocean (low temperatures, high salinity, and high pressure), together with the hydrocarbon contamination, favor the natural selection of polyextremophilic microorganisms, which have gained the attention of biotechnologists due to their metabolic diversity and their ability to produce secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the results related to the presence of enzymes involved in oil degradation are consistent with previous works of our own and other groups that investigated the Mexican exclusive economic zone and identified oil-degrading microorganisms derived from 16S amplicon analysis (Fernanda Sánchez-Soto Jiménez et al, 2018;Godoy-Lozano et al, 2018;Hernández-López et al, 2019;Moreno-Ulloa et al, 2019;Raggi et al, 2020;Ramírez et al, 2020); isolated fractions related to petroleum (Moreno-Ulloa et al, 2019); isolated consortia and species capable of degrading petroleum under aerobic and anaerobic conditions (Muriel-Millán et al, 2019;Curiel-Maciel et al, 2021;Rosas-Díaz et al, 2021); and characterized petroleum-degrading enzymes (Rodríguez-Salazar et al, 2020), even in regions with no evidence of anthropogenic perturbation. A recent review illustrated the distribution of bacteria in the water column and sediments of the Mexican exclusive economic zone of the GoM (Rodríguez-Salazar et al, 2021). The identification of all samples amplified using the V3-V4 16S rRNA gene variable regions showed that members of oil-degrading genera were distributed in the water column throughout the region extending from Perdido (Tampico) to Campeche Bay.…”
Section: Identification Of Overrepresented Pathwaysmentioning
confidence: 99%